Atoms in Generalized Orbital Configurations: Towards Atom-Dedicated Density Functionals - Toader, Ana Maria (Int J Mol Sci, 2019)
Deriving a practical formula for the atomic body with generalized shell occupations, we perform a detective analysis of the radial distribution in the exchange energy, hinting at ideas about new types of density functionals, dedicated to the specifics of the electronic structure of atoms, exploiting the intrinsic spherical symmetry.